Genomic Characterisation of Campylobacter jejuni Isolates Recovered During Commercial Broiler Production - Truccollo, Brendha; Whyte, Paul; Burgess, Catherine M.; Bolton, Declan J. (Frontiers in Microbiology, 2021)
Background: Campylobacter are commonly transmitted to humans from chickens. Campylobacter jejuni is the species most frequently associated with human illness, and the most prevalent species recovered from poultry. Objective: The objective of this study was to analyse a sub-population of C. jejuni from two broiler flocks on the farm and at slaughter using whole genome sequencing to gain insights into the changes in the Campylobacter population during broiler production, including changes in virulence and antimicrobial resistance profiles. Methods: In this study, ten composite faecal samples, obtained by pooling 10 fresh faecal samples, were collected in the broiler house on two farms on days 14, 21, 28 and 34 (n = 80) and ten composite (10 pooled) caecal samples were collected at the time of slaughter for each flock (n = 20). These were tested for C. jejuni using the ISO 10272-2:2016 method. Seven isolates were randomly selected from each of the nine Campylobacter-positive sampling points (n = 63) and were subjected to antimicrobial susceptibility tests. Their genomes were sequenced and the data obtained was used to characterise the population structure, virulence, antimicrobial resistance determinants and inter-strain variation. Results: The Farm 1 isolates had three MLST types (ST257-257, ST814-661, and ST48-48) while those on Farm 2 were ST6209-464 and ST9401. Interestingly, only the MLST types with the greatest number of virulence genes tested for persisted throughout the production cycle, and the detection of antimicrobial resistance determinants (gyrA T86I, tetO) increased after thinning and at slaughter, with the detection of new strains. Conclusion: The persistence of the most virulent strains throughout the production cycle has important implications for the risk to consumers and requires further investigation. The detection of new strains within the population corresponding with the time of thinning and transportation reflects previous reports and provides further evidence that these activities pose a risk of introducing new Campylobacter strains to broiler batches.